PEMANFAATAN YOUTUBE SEBAGAI SUMBER BELAJAR PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS 2 DI SD MUHAMMADIYAH GKB 2 GRESIK - Natasya Shofiyatun Nisa; Mohammad Ahyan Yusuf Syabani (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2026)
This study examines the use of YouTube as a learning resource in Islamic Religious Education (PAI) learning for grade 2 students of SD Muhammadiyah GKB 2 Gresik. The research problem focuses on the lack of variation in learning media used, so that students tend to get bored and are less motivated in understanding PAI material. The main objective of this study is to comprehensively describe the implementation of YouTube as a PAI learning medium and analyze the impact on students' interests and understanding. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis. The results showed that the use of YouTube significantly increased students' interest, motivation, and understanding of PAI material. Visual and interactive content on YouTube helps students understand abstract concepts more concretely, and encourages the development of critical thinking skills and digital literacy. However, there are several obstacles such as time constraints and lack of digital literacy among teachers and students. This study recommends the need for digital literacy training for teachers, provision of supporting facilities, and supervision in content selection so that the use of YouTube can run optimally. The results of the study are expected to be a reference in developing innovative PAI learning strategies that are relevant to technological developments.